AN INQUIRY ON THE STUDENTS’ WRITING COMPETENCE OF ANALYTICAL EXPOSITION TEXT - Samsul Amri (EJI (English Journal of Indragiri) : Studies in Education, Literature, and Linguistics, 2017)
Writing competence has been being appealing topic to investigate in order to achieve adequate and accurate final statement. One of the phenomena was on writing Analytical Exposition text. It is one of genres that is taught for Senior High School students. This existing study purposed to settle to what extent the students’ writing competence of Analytical Exposition text. To augment the objective, it was designed as survey research, which took 40 students of the elventh grade of SMA Muhammadiyah Tembilahan as the participants. They were asked for writing an Analytical Expostion text. The assessment aspects involved grammar, vocabulary, mechanics, fluency, and organization. After analyzing the data, the results display that the students’ competence on each of writing component was extremely diverse. Their grammar competence was 72.5, which was in good level, vocabulary mastery was 74.38, which was categorized as good level, mechanic mastery was 67.92, which was in enough level, fluency was in 64.17, which was classified as enough level, and organization was 68.33 which was in enough category. Then overall the students’ writing competence was 69.4 which was classified as enough level. It is suggested that they need to refine their performance to get better results.